PULSE PRESSURE AMPLIFICATION DIPPING PATTERN DURING SLEEP TIME: THE SAFAR STUDY. (June 2018) - Argyris, A.; Nasothimiou, E.; Aissopou, E.; Papaioannou, T.; Zhang, Y.; Blacher, J.; Safar, M.; Sfikakis, P.; Protogerou, A.
Abstract : Objective: The difference in pulse pressure (PP) between peripheral arteries and the aorta, called pulse pressure amplification (PPamp), is a well-described physiological phenomenon which is independently associated with cardiovascular events. Recent studies suggest that it exhibits circadian variability. Our aim was to evaluate the 24 hour profile of peripheral and central hemodynamics and detect the factors associated with the circadian variability of PPamp. Design and method: In 497 consecutive subjects (aged 54 years, 56.7% male, 79.7% hypertensives) we assessed the circadian pattern of peripheral and central arterial hemodynamics by 24-hour evaluation of brachial and aortic blood pressure (BP), augmentation index (AI) and pulse wave velocity (PWV) using a validated brachial-cuff based oscillometric device (Mobil-O-Graph). Results: All parameters exhibited a circadian variation. Sleep dipping (decrease) pattern was observed for PPamp (Figure 1), brachial and aortic systolic BP, mean BP (Figure 2) and PWV (Figure 3), whereas a rising pattern (higher sleep than wake values) was observed for brachial PP, aortic PP (Figure 4) and AI (Figure 5). The factors independently associated with the less sleep-dipping in PPamp were: older age, lower height, the use of antihypertensive medication, sleep decrease in arterial stiffness (PWV); whereas female gender, the presence of hypertension, sleep increase of pressure wave reflections (AI), sleep decrease in heart rate and mean BP were associated with a greater sleep-dipping in PPamp (Table 1). Figure. No caption available. Conclusions: These data provide further pathophysiological understanding of the mechanisms leading to PPamp dipping. Several implications regarding the clinical use of the aortic and brachial BP, especially during sleep time, are raised that should be addressed in future research.